MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VI MELALUI MEDIA PEMBELAJARAN CANVA DI UPT SD NEGERI MONDOKAN TUBAN - Ngui, Heni Hardianti; Juniatik, Ani; Nurfalah, Edy (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2025)
This study is a class action study (PTK) that aims to increase the learning motivation of grade VI students through the Canva learning media at UPT of Mondokan Tuban State Elementary School. The data collection techniques in this study were using observations, interviews, and anglers. The subjects in this study were 28 grade VI-B students. Based on observation results in cycle I, students' learning motivation has an average percentage of 77.2% with a fairly high criteria. Then, in cycle II the average learning motivation percentage was 81.2% with high criteria. In addition, based on the results of the lift in cycle I, the percentage of 77.8% was obtained with a fairly high criterion and the percentage of 82.5% with a high criterion was obtained in cycle II. Based on the results of the interview, the learning medium Canva can help students to understand the material more easily and enthusiastically participate in learning activities. This is due to Canva learning media which has interesting visualizations. The application of Canva learning media can make students interested in the material presented. Thus, Canva learning media can increase student learning motivation.